The Relationship Between Motivation and Job Satisfaction Among Teachers of Public Schools in Mafraq Province of Jordan - Nour Khaled Mashaqbah (European Scientific Journal, ESJ, 2018)
This study aimed at identifying the relationship between motivation and job satisfaction among teachers of public schools in Mafraq Province of Jordan. In order to do so, primary data were collected using self-completed questionnaires that were collected from (1260) public schools teachers, statistical analysis were used to analyze the relationships. The research has shown that: the degree of motivation among teachers of public schools in Mafraq Province is medium, as well as the degree of job satisfaction; and the research also showed that there is a statistically significant relationship between motivation and job satisfaction among teachers. The study showed that there is a lack of material incentives and bonuses, lack of a clear system of motivation that really measure the performance of the teachers, and lack of involvement of the teacher in decision-making. The results of this study suggest that in order to achieve a high and distinguished performance among the teachers, educational officials should consider working on the development of the laws, regulations and instructions of the system of bonuses and rewards commensurate with the requirements of the basic standard of living of the employees.